Progress in the Chemistry of Organic Natural Products 108 - Kinghorn, A. Douglas; Falk, Heinz; Gibbons, Simon; Kobayashi, Jun'ichi; Asakawa, Yoshinori; Liu, Ji-Kai (Progress in the Chemistry of Organic Natural Products,, 2019)
The first contribution summarizes current trends in research on medicinal plants in Mexico with emphasis on work carried out at the authors' laboratories. The most relevant phytochemical and pharmacological profiles of a selected group of plants used widely for treating major national health problems are described. The second contribution provides a detailed survey of the so far reported literature data on the capacities of selected oxyprenylated phenylpropanoids and polyketides to trigger receptors, enzymes, and other types of cellular factors for which they exhibit a high degree of affinity and therefore evoke specifice responses. And the third contribution discusses aspects of endophytic actinobacterial biology and chemistry, including biosynthesis and total synthesis of secondary metabolites produced in culture. It also presents perspectives fo the future of microbial biodiscovery, with emphasis on the seondary metabolism of endophytic actinobacteria.